2020
DOI: 10.14689/ejer.2020.85.6
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Attitude towards Science Scale: A Validity and Reliability Study

Abstract: This study aimed to develop an attitude scale to find out middle school students' (grades 5 through 8) attitudes towards science and to investigate the effects of grade level on students' attitudes towards science. Research Method: Cross-sectional survey method was used in this study. The attitude towards the science scale developed by the researchers was applied to a sample of 691 middle school students. Fifth, sixth, seventh, and eighth-grade students' level of attitudes towards science were determined and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Yousaf (2018), asserts that Indonesia therefore, should adopt a model of supervision that fosters and stimulates creativity among students and teachers. As otherwise, the state of the education system will remain abysmal and students will not be able to compete in the market (Owan & Agunwa, 2019;Ozcan & Esra, 2020;Rusman, 2020). Indeed, humans are generally motivated by three things when it comes to choice of professions, that is, a posit power or authority, prestige, and monetary benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Yousaf (2018), asserts that Indonesia therefore, should adopt a model of supervision that fosters and stimulates creativity among students and teachers. As otherwise, the state of the education system will remain abysmal and students will not be able to compete in the market (Owan & Agunwa, 2019;Ozcan & Esra, 2020;Rusman, 2020). Indeed, humans are generally motivated by three things when it comes to choice of professions, that is, a posit power or authority, prestige, and monetary benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the students referred that their imagination and engineering skills were developed and that students wanted to choose STEM fields as a profession in the future. In the research carried out with 7th graders, Özcan & Koca (2019a) stated that STEM activities positively affect group work. Genç & Uğraş (2018) claimed that STEM activities encourage students to collaborative learning.…”
Section: Discussionmentioning
confidence: 99%
“…The results of statistical analysis based on EFA and CFA showed that the survey was reliable and acceptable to identify the STEM -A of high school students. The developed survey was not an adaptation of a survey as in other studies (Ozcan & Koca, 2019;Unlu et al, 2016;Yilmaz et al, 2017). The demographic characteristics of Turkish students were considered in the developed survey.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers (Guzey, Harwell, & Moore, 2014;Kier, Blanchard, Osborne, & Albert, 2014;Landicho, 2020) have developed surveys on attitudes towards STEM based on the demographics of their own country. Some researchers (Ozcan & Koca, 2019;Unlu, Dokme, & Unlu, 2016;Yilmaz, Koyunkaya, Guler, & Guzey, 2017) in our country adapted the developed STEM attitude surveys to our students. The aim of studies in this field should be to develop attitude survey considering the social and cultural structure of the country where students live.…”
Section: Review Of Literaturementioning
confidence: 99%